Dokumentų ir jų blankų informacinė-teisinė charakteristika - Dagytė-Juodpusienė, Anda (Knygotyra, 1986)
The concept of a document is being considered by many scientific disciplines from aspects peculiar to them.The definitions of the concept of a document from the position of juridical science and that of informatics have much in common.Principal features characterizing documents and their forms are defined in this article.Analysis of correlation of a document and its form is carried out in it.Original definition of the document’s form is suggested.Significance of a form can not be disregarded in the course of conducting All-Union system of unification of the forms of documents at present time.Unification is particularly vital in the field of the organizational and administrative documentation, which is one of the fields in which the unification to the greater part has been already carried out.The task of perfection of the form as a component part of the future document (its form) is important in introducing means in the automation of the information search, what will result in economy of labour expenditures, working and has to be regarded as a progressive process in the development of documentalistic.